Does Covid-19 Pandemic Change the Consumer Purchase Behavior Towards Cosmetic Products? - Mega Farisha; Hartoyo Hartoyo; Arief Safari (Journal of Consumer Sciences, 2022)
The Covid-19 pandemic has generally affected the cosmetic industry's marketing and sales. Drastic changes happened, and the sales now rely more on online sales. This study aimed to analyze the purchase behavior of facial serum cosmetic products before and during the Covid-19 pandemic. The sampling technique applied purposive sampling. Data analysis used Structural Equation Modelling - Partial Least Squares (SEM-PLS). Data were obtained from 200 respondents in the Jabodetabek area from April to May 2021, but only 163 were included in the analysis. The results show that the conditions before and during the pandemic are significant differences. Before the pandemic, co-creation, communal activation, conversation, halal awareness, and reference groups influenced the purchase behavior. On the other hand, though, reference groups did not affect the purchasing behavior during the pandemic. Therefore, business people in the cosmetics field can focus on co-creation and conversation.